Effects of electropulsing on inclusion size and corrosion-resistance of 304 stainless steel. Issue 12 (12th August 2020) - Jia, Danbin; Zhong, Liangcai; Yu, Jingkun; Zhou, Yuting; Liu, Zhaoyang; Tian, Chen; Wang, Jiawei; Dai, Wenbin
Abstract : Electropulsing has been imposed on molten AISI 304 stainless steel and its effects on the inclusion size and corrosion properties have been investigated. The average size of inclusions in electropulsing-treated samples was finer than that in untreated ones. A theoretical analysis shows that the mobility of solute atoms increases with electropulsing treatment. This promotes the nucleation of inclusions. Owing to a smaller inclusion size, the electrochemical experiments reveal that the pitting corrosion resistance of the electropulsing-treated stainless steel is significantly improved. The beneficial effects of electropulsing on the refinement of inclusions and the resistance to pitting corrosion increase with an increase in current density. Electropulsing treatment, therefore, provides a promising means to improve pitting corrosion resistance.